Hybridity and boundary-making: exploring the politics of hybridisation. Issue 4 (4th July 2017) - Kyed, Helene Maria
Abstract: Hybridity conveys the idea of the interweaving of practices, norms and identities that defy any compartmentalisation into fundamentally bounded entities. This results from processes of hybridisation whereby actors cross boundaries that are prominent at a given time, like state vs. traditional. Boundaries help consolidate power, hierarchies, and orders. This article discusses the politics of hybridisation in the constitution of authority in post-colonies, using the example of chiefs and state officials in Mozambique. It argues that hybrid acts also form part of individual actors' efforts to consolidate power and constitute authority and that this coexists in a productive tension with boundary-making.